The interscalar network of amazonian informal street vending in Yurimaguas, Peru - Mendoza-Santa Cruz, James; Díaz-Díaz, Donald; Curinuqui-Yahuarcani, Frand; Susuki-Rios, Sayuri (Frontiers in Built Environment, 2025)
Street vendors contribute significantly to the informal economy of cities, especially in developing countries such as Peru, where informal employment reaches 71.2%. This phenomenon is observed in the commercial dynamics in the Peruvian Amazon, where informal trade networks connect cities and rural areas through river transport. For this reason, the purpose of this study is to understand the socio-cultural and spatial dynamics of ambulatory trade in the El Vado market in Yurimaguas, Peru. Unlike traditional studies that are limited to a single scale of analysis, an inter-scale analysis is proposed, by integrating the territorial, urban and architectural scales. From a qualitative approach, semi-structured interviews were conducted, along with participatory observation, and documentary analysis. Commercial flows, seller profiles, types of merchandise, and occupation patterns between urban and rural areas were identified. The results highlight social and commercial networks at the regional level, as well as patterns of agglomeration, which temporarily transform streets into scenarios of economic and cultural interaction. Street vendors, with their sales modules, adapt to the characteristics of the place and municipal policies. In conclusion, the socio-cultural and territorial cohesion generated by these practices could contribute to implementing a plan for managing street vending and optimizing spatial relations in the city.